Hindu nation and its queers: Caste, islamophobia, and de/coloniality in India - Upadhyay, Nishant (Interventions: international journal of postcolonial studies, 2020)
Le jugement de la Cour suprême indienne de 2018 dépénalisant l'homosexualité a été qualifié d'"acte décolonial". Article 377, qui criminalisait l'homosexualité, était une loi coloniale introduite par les Britanniques en Inde, que l'État postcolonial a maintenue jusqu'en 2018. Le jugement peut être « décolonial » dans son intention, mais il y a d'autres processus simultanés en jeu qui ne sont pas si décoloniaux dans la pratique ; cet essai soutient que ces processus sont le colonialisme, la suprématie brahmanique et l'islamophobie. La violence basée sur la caste fait partie intégrante de l'hindouisme et est étroitement liée à d'autres matrices d'oppression, faisant de la caste le fondement de toute revendication de l'hindouisme en tant que queer, trans et non conforme au genre amical. Étudiant les récentes réponses nationalistes hindoues en faveur de la dépénalisation de l'homosexualité en Inde, cet essai retrace comment la droite hindoue déploie la queerness pour propager ses agendas islamophobes, castistes et homohindunationalistes. L'essai défend la décolonisation du droit, de l'État.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; cours; discours dominant; fem3400; inde; islamophobie; premier cycle; périodes historiques; queer; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppressions; thématiques; violences

Islamicate Sexualities: The Artworks of Ebrin Bagheri - Gayed, Andrew (esse arts + opinions, 2017)
As a push against colonial forces and imperialism, homosexuality in the Middle East was historically made into an illegal identity category—one that, many argue, did not exist prior to increased contact with Western explorers and travellers. It is important to understand how the emergence of the Gay International coincided with that of Western gay sexuality studies. These issues are all at the forefront in the study of Islamicate sexualities. “Islamicate,” as defined by Marshal Hodgson, refers not directly,to the religion of Islam itself, but to the social and cultural complexities historically associated with Islam, including non-Muslims living within the same regions. Only by keeping imperialism at the forefront of the study of sexualities can we better situate how pre-modern Islamicate sexual scripts have resisted complete colonization and continue to exist in the diaspora.
Keywords: LGBTQIA2+; amériques; approches et analyses; arts; asie; canada; cours; discipline; féminisme islamique; har4600; histoire de l'art; iran; premier cycle; queer; ressource en ligne; régions géographiques; thématiques

The rise of a gay and lesbian movement - Adam, Barry D. (Social movements past and present, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis